Non‐Fullerene Acceptors: Superior Noise Suppression, Response Time, and Device Stability of Non‐Fullerene System over Fullerene Counterpart in Organic Photodiode (Adv. Funct. Mater. 45/2020). (4th November 2020) - Jang, Woongsik; Rasool, Shafket; Kim, Byung Gi; Kim, Jehan; Yoon, Jinhwan; Manzhos, Sergei; Lee, Hang Ken; Jeon, Il; Wang, Dong Hwan
Abstract : In article number 2001402, Il Jeon, Dong Hwan Wang, and co‐workers report a comparison between non‐fullerene‐based sensitizers, eh ‐IDTBR, and conventional fullerene‐based acceptors in PBDTTT‐EFT‐based organic photodetectors. Greater absorption and better energy alignment of eh ‐IDTBR compared with the fullerene acceptor lead to the organic photodiode showcasing superior detectivity and response time.